Designing a Digital Platform for Sharing Resources - JÓNSDÓTTIR, GUÐRÚN EYDÍS (My University, 2017)
Digital sharing platforms have become popular in the past years. They allow their users to share anything they want, such as hobby equipment, transportation and other resources. In this context, sharing can be defined in different ways, for example selling and buying, renting, borrowing or giving. Popular platforms are for example, Airbnb, Uber and Blocket. This thesis explores the subject of designing these kind of platforms in order to identify challenges that might be encountered along the way. For the project work a case study of a platform called Tvättstugetid was used, which is a digital platform for people living in apartment buildings to book slots for their laundry facilities. The results were divided into a theoretical part where challenges were identified and discussed and a practical part where a prototype of the mobile layout for Tvättstugetid was designed, implemented and evaluated. During the case study problems and issues that arose were noted. These issues were grouped together and compared to other platforms. The identified challenges were access, coordination and tracking booked slots, privacy, communication and hierarchy of users. Further work will be needed to validate the results with an in-depth investigation of a wider range of platforms over longer period of time.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science